2016
DOI: 10.1111/eci.12583
|View full text |Cite
|
Sign up to set email alerts
|

The TyG index may predict the development of cardiovascular events

Abstract: The TyG index, a simple measure reflecting insulin resistance, might be useful to early identify individuals at a high risk of developing a cardiovascular event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
329
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(364 citation statements)
references
References 38 publications
27
329
7
1
Order By: Relevance
“…Notably, the cut-off point of 8.5 was quite different from the finding of 4.58 by Simental-Mendia [7], the reason for this may be explained by the different metabolic status among subjects from the two studies or the different ethnicities. The TyG level in our study was similar to that of other population from Korea [27, 32], America [33], France [30], and Spain [26], whereas the level of TyG in studies from Mexico was close to that of participants from Italy [31]. We also found that the diagnostic accuracy of TyG was superior to ALT, even if the optimal cut-off point of ALT was 20.5 U/L with a sensitivity of 66.1% and specificity of 65.9%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, the cut-off point of 8.5 was quite different from the finding of 4.58 by Simental-Mendia [7], the reason for this may be explained by the different metabolic status among subjects from the two studies or the different ethnicities. The TyG level in our study was similar to that of other population from Korea [27, 32], America [33], France [30], and Spain [26], whereas the level of TyG in studies from Mexico was close to that of participants from Italy [31]. We also found that the diagnostic accuracy of TyG was superior to ALT, even if the optimal cut-off point of ALT was 20.5 U/L with a sensitivity of 66.1% and specificity of 65.9%.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, there is growing interest in the TyG index. Several studies have reported that the TyG index was associated with the development of diabetes and cardiovascular diseases [26, 27]. Although the TyG index mathematical model was developed in Mexican population, our prior study showed that the TyG index was effective to identify the risk of insulin resistance (assessed by homeostasis model assessment of insulin resistance) in Chinese individuals [28].…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, IR is closely related to MetS. In addition, a recent study 27 showed that the TyG index could be a credible indicator for predicting the risk of a cardiovascular event. Therefore, we further investigated this diagnostic power of TyG for MetS.…”
Section: Discussionmentioning
confidence: 97%
“…compared the TyG index with the euglycemic‐hyperinsulinemic clamp test, and suggested that TyG could be useful for the identification of individuals with decreased insulin sensitivity in 2010 . A series of cohort and cross‐sectional studies confirmed a strong correlation between the TyG index and IR, type 2 diabetes mellitus, MetS, hypertension, cardiovascular events and fatty liver both in China and elsewhere. Published studies have shown that the TyG index is helpful for the prediction and early identification of individuals at high risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%